Features of Teleroentgenographic Indicators of the Position of the Teeth and the Profile of the Soft Tissues of the Face in Adolescents with Different Profiles and Types of Faces According to Schwarz A.M. - Prokopenko O.S; Gunas I. V; Beliaiev E. V; Kotsyura O. O; Kovalchuk V. V (Institute of Medico-legal Publications Pvt Ltd, 2022)
One of the most relevant areas of research in biomedical anthropology is the establishment of morphometric parameters of the human body, individual organs and structures of the body, in particular cephalometric indicators and indicators of the jaw-facial apparatus. Such research is important from the point of view of practical medicine, first of all improvement of methods of identification of the person in forensic medicine and for creation of a normative database for diagnostics of dental deformities and improvement of consequences of surgical, orthopedic and orthodontic interventions. One of the most accurate and effective methods for determining cephalometric parameters is the method of lateral teleroentgenography. The object: to establish teleroentgenographic indicators that characterize the position of teeth and the profile of facial soft tissues and determine their sexual characteristics in Ukrainian young men and young women with orthognathic occlusion depending on the profiles and types of faces according to Schwarz A. M. Conclusions: the results prove the need to consider not only age, but also sex, type and profile of the face for an individualized approach in determining the normative teleroentgenographic indicators of human, are important in forensic medicine to improve the efficiency of identification and in practical dentistry to assess the condition of the dental apparatus and ensure effective therapeutic and aesthetic results of orthopedic and orthodontic dentistry.